Introduction to international environmental law - Koivurova, Timo (Routledge, 2014)
"Introduction to International Environmental Law provides a concise overview of international environmental law and the relations and agreements among nations to facilitate environmental protection. Beginning by exploring the history nature and sources of international environmental law, Professor Koivurova moves on to consider the key principles as well as examining the implementation and effectiveness of international environmental law in practice. It considers how international environmental law has developed away from other branches of international law which are heavily based on state sovereignty, in order to more effectively facilitate environmental protection and concludes by posing questions about the future of the field.Taking a concise, accessible approach throughout and employing case studies drawn from a global range of examples, this book is the ideal first point of entry to the context, principles and issues of this important subject"--